Triagem fitoquímica e avaliação in vitro da atividade antimicrobiana do jatobá (Hymenaea Courbaril L.) contra patógenos alimentares - Leão, Geovanka Marcelle Aguiar (Universidade Federal do Tocantins, 2021)
There are several researches developed and directed to the discovery of new antimicrobial agents from plant extracts. A plant of great nutritional, pharmacological, medicinal and industrial importance is the species Hymenaea courbaril L., popularly known as jatobá that belongs to the family Fabaceae and presents numerous varieties. Samples of the leaves and fruits of jatobá were collected, dried, ground and submitted to the treatment with the Soxhlet extractor to obtain bioactive compounds. Antimicrobial properties of crude leaf and jatobá ethanolic extracts were tested with the well diffusion method and Minimum Inhibitory Concentration (MIC) against food-borne bacteria: Escherichia coli, Staphylococcus aureus, enteric enteric Salmonella serovar typhimurium, Bacillus cereus and Shiguella flexneri. The crude ethanolic extract of the fruit showed no antimicrobial activity against all the pathogens tested. The extracts of the leaf at the concentrations of 200, 100 and 50 mg/mL showed antimicrobial action against S. aureus, B. cereus and S. flexneri when using the well diffusion method for E. coli and S. typhimurium, resistant to the method. In the MIC test the S. flexneri and B. cereus strains were inhibited at all concentrations tested, while for S. aureus the inhibition was only present at the concentration > 6.25 mg/mL. The ethanolic extract of leaves of jatobá showed to be efficient in the lowest concentrations against S. flexneri and B. cereus. In the phytochemical analysis, carotenoids, saponins, alkaloids, tannins, sterols and triterpenoids were identified that are compounds with antimicrobial potential. The ethanolic extract of the leaf presents potential to be used as a natural alternative to the control of these foodborne pathogens.